1995
DOI: 10.1111/j.1525-1446.1995.tb00156.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐Related Concerns and Educational Needs of Public Health Nurses in a Rural State

Abstract: An anonymous questionnaire was completed by 369 nurses in public health departments in a rural Southeastern state to examine the relationship between nurses' prior HIV training and their HIV-related knowledge, attitudes, concerns, and perceived training needs. The survey was conducted in three predominantly urban counties with the highest number of AIDS cases and in 38 rural counties with two or fewer reported AIDS cases. Knowledge answers were generally 70%-90% correct and attitudes more favorable than unfavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…In fact, one study that compared AIDS in women in urban and rural Georgia found that the survival time for women in the urban area was signi cantly greater than that of women from areas outside Atlanta (Whyte & Carr, 1992). Rural nurses are more numerous, and may be important resources for care of women with HIV/AIDS in rural communities (Carwein et al, 1993;Sowell & Opava, 1995), but rural nurses express more concern about working with persons with AIDS than urban nurses (Highriter et al, 1995;Koch et al, 1991), and a strong desire for greater training and education surrounding HIV/AIDS (Highriter et al, 1995;Koch et al, 1991).…”
Section: Issues In Service Deliverymentioning
confidence: 94%
“…In fact, one study that compared AIDS in women in urban and rural Georgia found that the survival time for women in the urban area was signi cantly greater than that of women from areas outside Atlanta (Whyte & Carr, 1992). Rural nurses are more numerous, and may be important resources for care of women with HIV/AIDS in rural communities (Carwein et al, 1993;Sowell & Opava, 1995), but rural nurses express more concern about working with persons with AIDS than urban nurses (Highriter et al, 1995;Koch et al, 1991), and a strong desire for greater training and education surrounding HIV/AIDS (Highriter et al, 1995;Koch et al, 1991).…”
Section: Issues In Service Deliverymentioning
confidence: 94%
“…12 However, this is at variance with various studies done in Nigeria which found that there is high prevalence of negative, stigmatizing and discriminatory attitudes to the care of PLWHA among health care workers in Nigeria including nurses. 10,20,21,30 The difference may be attributed to various in-service trainings on HIV/AIDS and awareness campaigns that are being carried out in Nigeria recently, which has been shown to positively change attitudes and perceptions of people towards HIV disease. 31 This may represent a new evidence suggesting recent change in the attitude of Nigerian Nurses towards the care of PLWHA.…”
Section: Discussionmentioning
confidence: 99%
“…9,22,23,32 Interestingly, some respondents identified fear of losing one's job if one contract HIV/AIDS, this buttresses the call to make working environment safe and ensure job security for the staff taking care of PLWHA. 30 There was a significant relationship between the professional cadre of nurses and their attitude towards the care of HIV/AIDS patients. This is similar to the findings of A South African study done among nurses caring for HIV/AIDS patients at public hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Higher degrees of fear were correlated with increased support for both types of testing. Lack of knowledge among nurses about their actual risk of infection and about postexposure prophylaxis may be the main reason for a high degree of fear [12][13][14] ; in our survey, 25% of respondents reported that they had never received any HIV/AIDS training. Knowledge and practice could reduce the high degree of fear.…”
Section: Resultsmentioning
confidence: 97%